The blue zone : lessons for living longer from the people who've lived the longest - Buettner, Dan. (Washington, D.C. : National Geographic, 2008)
National Geographic explorer Dan Buettner has traveled the globe to uncover the best strategies for longevity found in the Blue Zones: places in the world where higher percentages of people enjoy remarkably long, full lives. Here he discloses the recipe, blending this unique lifestyle formula with the latest scientific findings to inspire easy, lasting change that may add years to your life. Buettner's research effort, funded in part by the National Institute on Aging, has taken him from Costa Rica to Italy to Japan and beyond. In the societies he visits, it's no coincidence that the way people interact with each other, shed stress, nourish their bodies, and view their world yields more good years of life. By observing their lifestyles, Buettner's teams have identified critical everyday choices that correspond with the cutting edge of longevity research--and distilled them into a few simple but powerful habits that anyone can embrace.--From publisher description.
Keywords: Longevity; Medical geography; Blue zones